Analog backlog: Pressing records during the vinyl revival. Issue 4 (19th December 2017) - Palm, Michael
Abstract: After sustained growth for over a decade among independent record labels and retail outlets, major labels and chain stores embraced vinyl records as a growth sector, and for the first time in half a century, demand began outpacing supply. In this essay, I analyze recent trends of vinyl traffic and critique a prominent feature of contemporary vinyl culture: Record Store Day. The annual holiday has boosted vinyl sales while become an inflationary engine driving up costs, which alongside sales have skyrocketed since the turn of the century. At stake is a sustainable supply chain for recorded popular music that is not beholden to online access to digitized content and that can thrive outside the grip of corporate retail machinery. I describe how pressing plants and independent labels are coping with the surge in demand for vinyl records, and to conclude I suggest how supporters and scholars of independent music can more effectively combat corporate control by decoupling it from digitization as two distinct phenomena. For lovers as well as makers of independent music, the major labels' reembrace of an analog format like vinyl can be as threatening as the corporate stranglehold on digital distribution.